2005
DOI: 10.1111/j.1463-1318.2005.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency anaemia – useful diagnostic tool for right sided colon cancers?

Abstract: Anaemia is a poor predictor of right-sided colon cancers and cannot be used as an effective investigative tool in symptomatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…Blood loss is present in 60% of CRC cases, and a daily loss of as little as 3 mL in the stool can cause iron deficiency anemia [15]. However, as only 18% of CRC cases had anemia more than a year before diagnosis [16], a significant proportion of the population is not anemic [17]. The fecal occult blood test detects only current bleeding, while in CRC, blood loss is commonly intermittent [10].…”
mentioning
confidence: 99%
“…Blood loss is present in 60% of CRC cases, and a daily loss of as little as 3 mL in the stool can cause iron deficiency anemia [15]. However, as only 18% of CRC cases had anemia more than a year before diagnosis [16], a significant proportion of the population is not anemic [17]. The fecal occult blood test detects only current bleeding, while in CRC, blood loss is commonly intermittent [10].…”
mentioning
confidence: 99%
“…However, wide variations of Hb levels among cancer patients, or even the general population, have been extensively reported, making it difficult to diagnose anemia solely based on a single measurement of Hb level at baseline. The newest updated NCCN guideline suggested that a drop of as little as 2 g/dL in Hb level, even in non-anemic patients with a high baseline Hb level, is an alarming indicator for the presence of anemia [3,24-26]. Nonetheless, as yet there has been no report systemically evaluating the role of post-diagnosis change of Hb level in predicting cancer patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Occurrence of anemia varies considerably between different types of cancers 3, 4. Despite high prevalence at cancer diagnosis, anemia as assessed through hemoglobin concentration has been found to function poorly as a diagnostic tool 8–10…”
mentioning
confidence: 99%